It's fundamental: Welfare theorems, market failures, and the turn from "public finance" to "public economics" - Steven G. Medema (Duke University, Center for the History of Political Economy (CHOPE), 2022)
In a paper delivered at the December 1955 meeting of the Econometric Society, Paul Samuelson noted that though economists had done "work of high quality and great quantity in the field of taxation," the theory of public expenditure had been "relatively neglected" (1958, 332). Anglo-American treatments of the subject, which in the late 19th century began to take the form of the self-contained treatise, typically opened with a brief, almost obligatory statement of the proper functions of the state before launching into their extensive disquisitions on sundry aspects of taxation, public debt and, eventually, fiscal policy. The operative point here is that these roles assigned to the state were asserted, and typically briefly, rather than demonstrated, even if the tasks ascribed-e.g., national defense, a system of justice, public works-resonate with modern theoretical sensibilities. The last third of the twentieth century, though, saw a significant structural change in this pattern. While the analysis of taxation and other financing issues did not disappear (and, in the case of taxation, continue to expand in scope), the cursory treatment of the functions of the state slowly gave way to deeper and more systematic inquiries. Indeed, by the mid-1980s the 'public expenditure theory' lacuna lamented by Samuelson had largely been filled with the theories of public goods, externalities, marginal-cost cum peak-load pricing. This paper documents and attempts to explain this transformation, locating its origins in Richard Musgrave's normative theory of the public household and the adoption by subsequent thinkers of new developments in welfare theory, which was seen to offer a theoretically sophisticated a vision of the state's role as a response to the problem of market failure.
Keywords: B2; D5; D61; D62; D7; H00; 330; Public Finance; Public Economics; Welfare Economics; Externalities; Public Goods; Cost-Benefit Analysis; Musgrave